The alkaloids : chemistry and biology. - Cordell, Geoffrey A., 1946- (Academic Press, 2010)
Alkaloids make up a major group of natural products derived from a wide variety of organisms, and are widely used as medicinal and biological agents. Each volume in this series provides detailed coverage of particular classes or sources of alkaloids.